2012
DOI: 10.1007/s00284-012-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhi Plasmid Impairs Dendritic Cell Responses to Infection

Abstract: Salmonella enterica serovar Typhi (S. typhi) evades from innate immunity by expression of a variety of pathogenic factors. The "pR(ST98)" plasmid of S. typhi is involved in multidrug-resistant and virulence of S. typhi. However, its exact effect on host cell function remains elusive. Dendritic cells (DCs) play an important role in shaping immune response against Salmonella. For the purpose of investigation whether pR(ST98) might target DCs involved in adaptive immune response, murine DCs were infected with S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Salmonella enterica serovar Typhimurium interferes with the migration of intestinal DCs and hinders antigen presentation via the ubiquitination and degradation of MHC class II molecules, which prevents bacterial killing [5], [6]. Helicobacter pylori replicates within autophagosomes and retains cytosolic MHC class II molecules; H. pylori also prevents interleukin (IL)-12 production and induces IL-10 secretion, thereby inhibiting the anti-microbial Th1 response [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella enterica serovar Typhimurium interferes with the migration of intestinal DCs and hinders antigen presentation via the ubiquitination and degradation of MHC class II molecules, which prevents bacterial killing [5], [6]. Helicobacter pylori replicates within autophagosomes and retains cytosolic MHC class II molecules; H. pylori also prevents interleukin (IL)-12 production and induces IL-10 secretion, thereby inhibiting the anti-microbial Th1 response [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…For Salmonella, the induction of macrophage apoptosis is a specific virulence mechanism promoting cell-to-cell spread in vivo. As reported previously, S. typhi harboring pR ST98 had the potential to enhance macrophage apoptosis rate and to restrain DCs autophagy (8,9). However, its exact effect on apoptosis and autophagy in infected macrophages remains elusive.…”
Section: Ntroductionmentioning
confidence: 78%
“…Here we utilized RAPA to study the effect of plasmid pR ST98 on the interaction between bacterial virulence and autophagy of macrophages J774A.1. Previous data demonstrated that pR ST98 was related with the apoptosis of macrophages through the (8,9), whether the plasmid affects macrophage autophagy is unknown. The inhibition of autophagy in S. typhi-WT infected macrophages was observed in this study; however, there remains the question as to what role pR ST98 plays in the relationship between autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations